Highly Selective Dual-Mode Microstrip Bandpass Filters Using Triangular Patch Resonators - K.G. Avinash; I. S. Rao (Advanced Electromagnetics, 2017)
In this paper, highly selective dual-mode microstrip bandpass filters are proposed using horizontal and vertical slots formed on the surface of a triangular patch. Slots are responsible for splitting and coupling of dual degenerate modes and also facilitate in controlling their resonant frequencies by varying the dimensions of the slots. Horizontal and vertical slots reroute the direction of the flow of current on the surface of the patch, which results in switching of transmission zeros. Two 2-pole and one 4-pole dual-mode filters are designed, simulated and fabricated. Two pole filters have transmission zeros on side of the passband and four pole filter have transmission zeros on both sides of the passband. The designed filters exhibit a fractional bandwidth of less than 7 % and there is a good agreement between simulated and measured results.